1999
DOI: 10.1080/02827589950154113
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bare Root Spruce Seedlings with Permethrin against Pine Weevil before Lifting

Abstract: The possibility of applying permethrin on coniferous bare root seedlings to protect them against pine weevil (Hylobius abietis L.) in the transplant lines may avoid or diminish problems connected with dipping or spraying plant bundles with the insecticide after lifting. Spraying 0.5 or 1% permethrin solution on bare root spruce seedlings in the transplant lines resulted in initial amounts of about 0.35 and 0.74 mg permethrin mm − 2 bark on the lower part of the plant stem. This amount diminished during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Few studies reporting on permethrin dissipation from foliage over the time frame of the present study were found. Many shorter term studies reported the decline of permethrin residues on foliage following sprays and estimated half‐lives ranging from 2 to 14 days (Antonious, 2021; Heshmati et al, 2020; Knepper et al, 1996; Southwick et al, 1983; Sundraram et al, 1992; Torstensson et al, 1999; Willis et al, 1992, 1994). A pair of longer term studies reported detectable permethrin residues on plants up to 2 years after a spray (Sundraram et al, 1992; Torstensson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies reporting on permethrin dissipation from foliage over the time frame of the present study were found. Many shorter term studies reported the decline of permethrin residues on foliage following sprays and estimated half‐lives ranging from 2 to 14 days (Antonious, 2021; Heshmati et al, 2020; Knepper et al, 1996; Southwick et al, 1983; Sundraram et al, 1992; Torstensson et al, 1999; Willis et al, 1992, 1994). A pair of longer term studies reported detectable permethrin residues on plants up to 2 years after a spray (Sundraram et al, 1992; Torstensson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Many shorter term studies reported the decline of permethrin residues on foliage following sprays and estimated half‐lives ranging from 2 to 14 days (Antonious, 2021; Heshmati et al, 2020; Knepper et al, 1996; Southwick et al, 1983; Sundraram et al, 1992; Torstensson et al, 1999; Willis et al, 1992, 1994). A pair of longer term studies reported detectable permethrin residues on plants up to 2 years after a spray (Sundraram et al, 1992; Torstensson et al, 1999). Both showed an initial rapid decline within approximately 1 month of the spray, in agreement with the previously mentioned half‐lives.…”
Section: Discussionmentioning
confidence: 99%
“…Seedlings can be treated in three different ways: treatment of seedlings in the nursery directly on the flowerbed before picking, dipping the aboveground part of bundles in insecticidal solution before planting, spraying the seedlings with insecticide after planting (Torstensson et al 1999;Varínsky 2011).…”
Section: Chemical Protection Of Seedlingsmentioning
confidence: 99%
“…The pine weevil has been controlled in Ireland and elsewhere mainly by applying chemical pesticide (most recently cypermethrin or α-cypermethrin) to replanted seedlings before and/or after planting (e.g. Torstensson et al, 1999;Willoughby et al, 2004). EPN, as part of an integrated pest management strategy, are intended to help replace cypermethrin and α-cypermethrin as their use is phased out in the European Union under sustainable forest management (SFM) policies.…”
Section: Conclusion and Risk Evaluationmentioning
confidence: 99%